SM09419, a Novel, Small-Molecule CDC-like Kinase (CLK) Inhibitor, Demonstrates Strong Inhibition of the Wnt Signaling Pathway and Antitumor Effects in Mantle Cell Lymphoma Models - Chung, Heekyung; Creger, Emily; Sitts, Lauren; Chiu, Kevin; Mak, Chi-Ching; KC, Sunil; Tam, Betty; Bucci, Gail; Stewart, Josh; Phalen, Timothy; Cha, Steven (Blood, 2019)
Mantle cell lymphoma (MCL) is a B-cell non-Hodgkin lymphoma (NHL) that accounts for ~7% of all NHL in the U.S. MCL is associated with aberrant activation of the Wnt signaling pathway, which plays a key role in the survival and maintenance of MCL-initiating cells. Many MCL patients experience relapse and subsequent disease progression due to chemoresistance following initial therapy; hence, novel therapies are needed. CLKs regulate the activity of serine/arginine-rich splicing factors (SRSFs) that modulate spliceosome assembly, mRNA splicing, and gene expression. SM09419 is a novel, oral, small-molecule pan-CLK inhibitor that potently inhibits the Wnt pathway. The purpose of these studies was to examine the antitumor activity of SM09419 in preclinical models of MCL. SM09419 potently inhibited both CLK1-CLK4 (IC50 for all <0.02 µM) and Wnt signaling pathway (average EC50=0.068 µM) activities. In REC-1 and GRANTA-519 MCL cells, SM09419 dose-dependently inhibited SRSF6 phosphorylation and potently suppressed expression of Wnt-related genes (CCND1, LEF1, TCF7) and proteins vs. vehicle. In tests on 5 MCL cell lines, cell proliferation was strongly impaired by SM09419 across all lines (average EC50=0.102 µM [0.021-0.236]). SM09419 also induced apoptosis in REC-1 and GRANTA-519 cells, increasing caspase 3/7 activation and PARP cleavage while reducing survivin and MCL-1 expression vs. vehicle. In vivo antitumor effects and tolerability of oral SM09419 (QD 20-21 days) were assessed in mice bearing REC-1 and JeKo-1 flank xenografts (n=5/group). In REC-1 xenografts, strong tumor growth inhibition (TGI) vs. vehicle occurred in mice treated with 12.5, 25, and 50 mg/kg SM09419 (TGI 88% [p<0.01], 100%, and 100% [p<0.001], respectively), and the two highest doses induced complete tumor regression in all mice from D14. Similarly, in JeKo-1 xenografts, SM09419 (12.5 and 25 mg/kg) induced significant TGI vs. vehicle (71% and 100%, respectively; p<0.0001) with complete tumor regression at 25 mg/kg, whereas acalabrutinib (50 mg/kg BID) was not efficacious (27% TGI) when tested in parallel. SM09419 25mg/kg induced reversible suppression of phospho-SRSF6 protein and inhibited Wnt pathway-related gene expression (TCF7 and DVL2) in JeKo-1 tumors in a single-dose PD study, demonstrating downstream target engagement in vivo. SM09419 was also assessed in 2 patient-derived xenograft (PDX) mouse models of MCL. PDX cells were injected intravenously and treatment was initiated upon 8-12% engraftment of human CD45+CD19+ cells in peripheral blood. In the first model, derived from a patient who was progressive after 8 modalities including ibrutinib, SM09419 (25 mg/kg QD) increased survival vs. vehicle (100% through D26 vs. 0% by D12, respectively; n=6/group) and suppressed MCL engraftment in the blood (12% at D26 vs. 69% at D8 and D12, respectively; p=0.002) and bone marrow (30% at D26 vs. 91% at D8 and D12, respectively; p=0.002). In the second model, derived from a patient refractory after ibrutinib and anti-PDL1 treatment, SM09419 (25 mg/kg QD) significantly suppressed MCL engraftment vs. vehicle in the blood (8% vs. 72%), bone marrow (20% vs. 57%), and spleen (15% vs. 96%) at D28 (study end; p<0.001 for all; n=4/group). In addition, SM09419 greatly inhibited splenomegaly vs. vehicle (0.04 g vs. 0.4 g, respectively; p<0.001). In a subsequent experiment in the same model, mice (n=7/group) were treated with 12.5 or 25 mg/kg SM09419 or vehicle for 12 weeks (to D85). Blood MCL engraftment at D41 was significantly lower in mice treated with SM09419 (40% at 12.5 mg/kg and 23% at 25 mg/kg) vs. vehicle (88%; p<0.01 and p<0.001, respectively). SM09419 dose-dependently increased survival (28.6% at 12.5 mg/kg and 85.7% at 25 mg/kg at D85) vs. vehicle (0% at D63); survival was maintained in both dose groups during post-treatment monitoring (to D99). SM09419 was well tolerated in all tested mouse models based on body weight measurements. In summary, SM09419 potently inhibited SRSF6 phosphorylation Wnt signaling pathway activity, and cell proliferation and induced apoptosis in MCL cell lines. The strong in vivo antitumor effects observed as a single agent suggest that SM09419 may provide a clinical benefit for patients with treatment-resistant or refractory MCL. A Phase 1 study assessing safety, tolerability, and pharmacokinetics of SM09419 in subjects with advanced hematologic malignancies is being initiated. Chung:Samumed, LLC: Employment, Equity Ownership. Creger:Samumed, LLC: Employment, Equity Ownership. Sitts:Samumed, LLC: Employment, Equity Ownership. Chiu:Samumed, LLC: Employment, Equity Ownership. Mak:Samumed, LLC: Employment, Equity Ownership. KC:Samumed, LLC: Employment, Equity Ownership. Tam:Samumed, LLC: Employment, Equity Ownership. Bucci:Samumed, LLC: Employment, Equity Ownership. Stewart:Samumed, LLC: Employment, Equity Ownership. Phalen:Samumed, LLC: Employment, Equity Ownership. Cha:Samumed, LLC: Employment, Equity Ownership.